Mathematics Learning Innovation through Group Investigation-Based E-Comic Media to Improve Junior High School Students' Resilience - Rasilah; Yaya S. Kusumah; Dadang Juandi; Dadan Dasari; Jajang Rahmatudin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
This study aims to develop and test the effectiveness of integrated mathematics learning media based on E-Comics with the Group Investigation learning model in improving mathematics retention and learning outcomes of junior high school students. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The product developed is a learning tool consisting of a syllabus, lesson plans, student worksheets (LKPD), mathematics e-comics, and a mathematical ability representation test. The subjects of this study were seventh-grade students of SMP Darul Ma'arif Indramayu NU in the 2025/2026 academic year. Data were collected through expert validation sheets, student response questionnaires, observations of learning implementation, and pretests and posttests. The results of the study indicate that the mathematics media based on the Group Investigation E-comics was declared very valid by experts in terms of material, media, and language with an average value above 88%. The media was also declared practical and a good learning implementation based on positive student responses. After being tested for its effectiveness, the mathematics e-comics were able to improve students' resilience in mathematics by increasing perseverance, motivation, and positive attitudes in solving mathematical problems. The contribution of this study is to make learning more effective, especially for materials that are considered boring or complex for students. Thus, the mathematics learning media based on the Group Investigation E-comics model is worthy of being used as an innovative alternative in junior high school mathematics learning.